On considere les expressions suivantes E= (2x+5)(7x+1) et F=(7-2x)(7+2x)

1. Développer et réduire E.
2.Développer et réduire F.
3. Développer et réduire E+F

2
E= 2X x 7X +2X x 1 + 5 x 7X +5 x 1
E= 14X + 2X + 35X+5
E= 46X+5

Réponses

2014-04-15T09:39:21+02:00
Bonjour

E = (2x+5)(7x+1)
   = 14x² + 2x + 35x + 5
   = 14x² + 37x + 5

 
F = (7 - 2x)(7 + 2x)
    = 7² - (2x)²
    = 49 - 4x²

E + F = (14x² + 37x + 5) + (49 - 4x²)
         = 14x² + 37x + 5 + 49 - 4x²
         = 10x² + 37x + 54
Meilleure réponse !
  • Utilisateur Brainly
2014-04-15T09:41:52+02:00
On considère les expressions suivantes E= (2x+5)(7x+1) et F=(7-2x)(7+2x)
1. Développer et réduire E.

E= (2x + 5)(7x + 1)
E= 14x² + 2x + 35x + 5
E= 14x² + 37x + 5

2.Développer et réduire F.

F= (7 - 2x)(7 + 2x)
F= 49 + 14x - 14x - 4x²
F= - 4x² + 49

3. Développer et réduire E + F.

EF= (2x + 5)(7x + 1) + (7 - 2x)(7 + 2x)
EF= 14x² + 2x +35x + 5 + 49 + 14x - 14x - 4x²
EF= 10x² + 37x + 54